The Relevance of Relatives and Friends: Subjective Norms and Social Networks Driving Young Macedonians’ COVID-19 Vaccine Decisions - Geegan, S. A.; Palamidovska sterjadovska, Nikolina; Ciunova-shuleska, Anita; Ivanov, B.; Pfeiffer, S., & Adam, T (Common Ground Research Networks, The International Journal of Interdisciplinary Social and Community Studies, 2024)
Abstract: As medical experts across the globe continue emphasizing the importance of COVID-19 vaccinations, Balkan nations have reported much lower immunization rates than their more affluent counterparts; this is particularly true in North Macedonia. Research is needed to better understand barriers and motivators to vaccine uptake. The current investigation employed a series of focus groups, framed through the theory of planned behavior, among young people in North Macedonia. The discussions revealed three key themes related to individuals’ attitudes, perceptions of subjective norms, and perceptions of behavioral control. Among both vaccinated and unvaccinated individuals, influenced by the collectivist culture, attitudes toward vaccination were tied to concerns about family members. Additionally, once again guided by the collectivist culture, individuals were strongly influenced by the vaccination norms established in their social networks. Finally, participants shared that the vaccine was widely available, and thus perceived behavioral control (i.e., access) did not represent a barrier to vaccine uptake. This insight creates a foundation of knowledge upon which interventions can be developed.
Keywords: Collectivism, Vaccine Hesitancy, Social Networks, Subjective Norms, Theory of Planned Behavior, COVID-19, Focus Groups